Adaptasi Rosenberg's Self-Esteem di Indonesia - M. Ahkam Alwi; Ahmad Razak (Seminar Nasional LP2M UNM, 2022)
Absrtact. Rosenberg's self-esteem scale is a widely used instrument. Rosenberg's self-esteem scale for Indonesian language adaptation has not been carried out specifically for high school students. This study aims to adapt the Indonesian language and test the validity and reliability. The subjects of this study were 275 high school students from several schools in the city of Surabaya. psychometric results show the factor loading analysis shows the fit model. The test results showed Goodness of Fit, namely GFI = 0.92, CFI = 0.99, and SRMR = 0.06. The item test results showed that 8 items had a loading factor of 0.63-082 and had a construct reliability of 0.899.  Key words: Self-Esteem, Students, Adaptation